Redo aortic root surgery post-Ross procedure - Bogachev-Prokophiev, Alexander; Sharifulin, Ravil; Demin, Igor; Karadzha, Anastasiia; Zheleznev, Sergey; Karaskov, Alexander; Afanasyev, Alexander; Pivkin, Alexey; Ovcharov, Mikhail; Zalesov, Anton; Murashov, Ivan; Tsaroev, Bashir; et al. (Frontiers in Cardiovascular Medicine, 2023)
Background: Despite numerous advantages of the Ross procedure, it presents a risk of late autograft and right ventricular outflow tract conduit failure. This study aimed to analyze the outcomes of autograft dysfunction reoperations using autograft-sparing and root replacement techniques. Methods: Between 2015 and 2023, 49 patients underwent redo root surgery in our institution. Autograft valve-sparing procedures (VSP) were performed in 20 cases and the Bentall procedure (BP) in 29 patients. The short and long-term clinical outcomes along with echocardiographic results of VSP and BP were investigated. Results: Overall early mortality rate was 2.0% with no significant difference between the groups. Severe autograft valve insufficiency at the time of redo (OR 4.07, P=0.03) and patient age (OR 1.07, P=0.04) were associated with a valve replacement procedure instead of VSP. The median follow-up duration was 34 months. No late deaths occurred in either group. Freedom from VSP failure and aortic prosthesis dysfunction were 93.8% and 94.1% in the VSP and BP groups, respectively. No reoperations were necessary in either group. Conclusion: Redo aortic root surgery can be safely performed in patients with autograft failure. Both root replacement and autograft valve-sparing procedures demonstrated acceptable results at mid-term follow-up. Early redo surgery pre-empting severe aortic insufficiency increases the likelihood of preservation of the dilated autograft valve.